TINGKAT KEBERHASILAN INSEMINASI BUATAN PADA INDUK SAPI SIMENTAL DI KECAMATAN PAGENTAN KABUPATEN BANJARNEGARA - Lamin; Rudi Salam; Soegeng Herijanto (Fakultas Peternakan. Unwiku, Purwokerto, 2024)
The purpose of this study was to determine the success rate of artificial insemination in cattle in Pagentan District, Banjarnegara Regency, and the success rate of farmers who performed artificial insemination. Because this area is one of the centers of beef cattle production in Banjarnegara Regency, it was deliberately chosen as the research location. The data collection technique used in this study was direct observation and interviews with farmers. The data obtained were calculated using the perception rate and service per perception formulas. According to the results of the study obtained in Pagentan District, most farmers were under 40 years old. While the level of education of the farmers was the highest, namely elementary school, with the main job mostly being being a farmer, The perception rate value obtained was 77.14% and was included in the high category because it exceeded the predetermined standard limit. While the service per conception value obtained was 1.29%, both of which indicate that the condition of livestock in Pagentan District is very good and has a high fertility rate, the birth interval value is not so long, which can affect the success rate of artificial insemination